Thalidomide pharmacokinetics in sheep. Issue 4 (3rd July 2016) - Smith, SL; Singh, P; Harding, D; Lun, D; Chambers, JP
Abstract: AIM: To determine the half life (T1/2 ), time taken to reach maximum plasma concentration (Tmax ) and maximum plasma concentration (Cmax ) of thalidomide in sheep following I/V, oral and topical treatment with a single dose of thalidomide. METHOD: Three groups of 4–6-month-old ram lambs were treated with thalidomide dissolved in dimethylsulphoxide (DMSO). The first group (n=10) was treated I/V with 100 mg thalidomide in 2 mL DMSO; the second group (n=8) received 400 mg thalidomide in 2 mL DMSO orally, and the third group (n=8) had 400 mg thalidomide in 4 mL DMSO applied topically. Plasma samples were collected up to 36 hours after treatment, snap-frozen at −80°C and analysed for concentrations of thalidomide using high performance liquid chromatography. RESULTS: Following I/V administration, T1/2 was 5.0 (SEM 0.4) hours, volume of distribution was 3, 372.0 (SEM 244.3) mL/kg and clearance was 487.1 (SEM 46.1) mL/hour.kg. Topical application of 400 mg thalidomide did not increase plasma concentrations. Following oral administration, thalidomide bioavailability was 89%, with T1/2, Tmax, and Cmax being 7.2 (SEM 0.8) hours, 3.0 (SEM 0.4) hours and 1, 767.3 (SEM 178.1) ng/mL, respectively. CONCLUSION: Topical administration using DMSO as a solvent did not increase concentrations of thalidomide in plasma. The mean pharmacokinetic parameters determined following oral treatment with 400 mg of thalidomide were similar to those reported in humans receiving a single 400 mg oral dose (T1/2 7.3 hours; Tmax 4.3 hours and Cmax 2, 820 ng/mL). There is potential for thalidomide to be used as a model for the treatment of chronic inflammatory conditions in sheep, such as Johne's disease, where tumour necrosis factor alpha plays a pathogenic role.